Self-repairing antibacterial aerospace cabin composite material and preparation method thereof
By combining functional components such as nano zinc oxide, copper-based metal organic frame and sulfur-containing microcapsules, a self-healing antibacterial space capsule composite material is designed, which solves the shortcomings of traditional materials in long-term antibacterial and self-healing capabilities. It achieves excellent stability and long-term performance in aerospace environment.
Patent Information
- Application Number
- CN202411801345.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Traditional space cabin materials have shortcomings in long-term antibacterial and self-healing capabilities, especially in aerospace environment, the stability and reliability of the materials still need to be verified.
By combining functional components such as nano zinc oxide, copper-based metal organic frames and sulfur-containing microcapsules, a self-healing antibacterial space capsule composite material was designed. The material achieves antibacterial through photocatalytic action under light conditions, and sulfur-containing microcapsules release sulfur radicals for self-healing when the material is damaged.
The coordinated enhancement of antibacterial properties and self-healing capabilities is achieved, and the material exhibits excellent stability and long-term performance in aerospace environment, extending the service life of the material.
Smart Images

Figure BDA0005178118190000141 
Figure BDA0005178118190000142 
Figure BDA0005178118190000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials for aerospace capsules, and in particular to a self-repairing antibacterial composite material for aerospace capsules and a preparation method thereof. Background Art
[0002] As human beings continue to explore the universe, spacecraft cabin materials are facing unprecedented challenges. During long space missions, the cabin must not only withstand external threats such as extreme temperature changes, high-energy radiation, and micrometeorite impacts, but also deal with the potential risks of internal microbial contamination. Although traditional spacecraft cabin materials have excellent mechanical properties and radiation resistance, they still have obvious deficiencies in long-term antibacterial and self-healing capabilities.
[0003] In the prior art, some researchers have tried to add antimicrobial agents directly to composite materials, or to apply antimicrobial coatings on the surface of materials. However, these methods often have problems such as rapid decay of antimicrobial effects and poor durability. On the other hand, although some self-healing materials perform well in ground applications, their stability and reliability in aerospace environments remain to be verified. In addition, there are very few attempts to organically combine antimicrobial and self-healing functions, not to mention their application in the aerospace field. Summary of the invention
[0004] The self-repairing antibacterial space capsule composite material of the present invention is designed to solve the above problems. By ingeniously combining functional components such as nano zinc oxide, copper-based metal organic framework and sulfur-containing microcapsules, the present invention achieves synergistic enhancement of antibacterial performance and self-repairing ability.
[0005] The object of the present invention is to provide a thermal self-repairing antibacterial aerospace capsule composite material, the composite material comprising the following components in parts by weight:
[0006] Epoxy resin matrix 100 parts;
[0007] Nano zinc oxide 0.5-5 parts;
[0008] 1-10 parts of copper-based metal organic framework;
[0009] 3-15 parts of sulfur-containing microcapsules;
[0010] 30-40 parts of curing agent;
[0011] Healing agent 5-20 parts.
[0012] Preferably, the epoxy resin matrix is bisphenol A epoxy resin, and its epoxy equivalent is 185-192 g / eq.
[0013] Preferably, the particle size of the nano zinc oxide is 20-30 nm, and the specific surface area is 30-50 m 2 / g.
[0014] Preferably, the copper-based metal organic framework is HKUST-1, with a specific surface area of 1500-2100m 2 / g, pore size is 0.9nm.
[0015] Preferably, the sulfur-containing microcapsules include polymethyl methacrylate shell material and tetraethylthiuram disulfide core material.
[0016] Preferably, the curing agent is triethylenetetramine, and its amine value is 440-460 mg KOH / g.
[0017] Preferably, the healing agent is triglycidyl isocyanurate, and its epoxy equivalent is 100-108 g / eq.
[0018] The method for preparing the self-repairing antibacterial space capsule composite material comprises the following steps:
[0019] (1) First, heat the epoxy resin matrix at 60-70°C and stir at a speed of 300-400 rpm;
[0020] (2) Secondly, slowly add nano zinc oxide and stir and disperse for 30-60 minutes;
[0021] (3) Then, add the copper-based metal organic framework and continue to stir and disperse for 30-60 minutes;
[0022] (4) Again, add the healing agent and stir evenly for 15-30 minutes;
[0023] (5) Then, add sulfur-containing microcapsules and stir gently for 10-15 minutes at a stirring speed of 100-200 rpm;
[0024] (6) Subsequently, vacuum degassing is performed at 70-80° C. for 15-30 minutes;
[0025] (7) Then, cool to 50-60°C, add curing agent, and stir rapidly for 3-5 minutes at a stirring speed of 400-500 rpm;
[0026] (8) Finally, the mixture was poured into a preheated mold, cured at 80-100°C for 2-4 hours, and then post-cured at 120-140°C for 2-4 hours, naturally cooled to room temperature, and demolded to obtain a composite material.
[0027] Preferably, the method further comprises the step of preparing a copper-based metal organic framework:
[0028] (1) First, a 1.0-1.2 mol / L Cu(NO3)2·3H2O aqueous solution and a 0.5-0.6 mol / L 1,3,5-benzenetricarboxylic acid ethanol solution were mixed in a volume ratio of 1:1;
[0029] (2) Secondly, stirring the reaction at 60-70°C for 8-12 hours;
[0030] (3) Then, the reaction product was cooled to room temperature and the precipitate was collected by centrifugation at a speed of 3000-4000 rpm for 10-15 minutes;
[0031] (4) Wash again with ethanol and deionized water three times each;
[0032] (5) Finally, vacuum dry at 80-90°C for 12-24 hours.
[0033] Preferably, the method further comprises the step of preparing sulfur-containing microcapsules:
[0034] (1) First, 5-10 wt% of polymethyl methacrylate is dissolved in dichloromethane to form an oil phase;
[0035] (2) Secondly, tetraethylthiuram disulfide is dissolved in the oil phase at a concentration of 10-20 wt %;
[0036] (3) Then, 1-3 wt% of polyvinyl alcohol is dissolved in deionized water to form an aqueous phase;
[0037] (4) Again, under stirring at 500-800 rpm, the oil phase was slowly added dropwise to the water phase at a rate of 2-5 mL / min to form an O / W emulsion;
[0038] (5) Then, stirring is continued at room temperature for 6-8 hours to evaporate the solvent and form microcapsules;
[0039] (6) Subsequently, the microcapsules were collected by centrifugation at a speed of 2000-3000 rpm for 5-10 minutes;
[0040] (7) Finally, wash with deionized water for 3 times and vacuum dry at 40-50°C for 12-24 hours.
[0041] From a molecular perspective, nano zinc oxide can generate photogenerated electron-hole pairs under light conditions, thereby generating superoxide free radicals (·O 2- ) and hydroxyl radicals (·OH). These active free radicals can effectively destroy bacterial cell membranes and achieve sustained photocatalytic antibacterial effects. At the same time, the porous structure of the copper-based metal organic framework (Cu-MOF) can not only adsorb and enrich bacteria, but also release Cu in a controlled manner. 2+ Ions achieve directional sterilization. Cu2+ Ions can bind to proteins on the bacterial cell membrane, destroying membrane integrity, or enter the cell and interfere with the active centers of enzymes.
[0042] What is even more innovative is that the sulfur-containing microcapsules in the present invention will rupture when the material is damaged, releasing sulfur-containing compounds (such as tetraethylthiuram disulfide). The SS bonds in these compounds break to form highly active sulfur free radicals, which then react with triglycidyl isocyanurate (TGIC) pre-dispersed in the matrix to form new covalent bonds, thereby achieving rapid self-repair of the material.
[0043] This multi-functional collaborative design not only solves the problem of rapid attenuation of the effect of traditional antibacterial materials, but also greatly extends the service life of the material through the self-repair function. More importantly, the present invention exhibits excellent stability in a simulated aerospace environment, which may be due to the formation of a unique protective network structure between the functional components, which mutually inhibits the degradation process in extreme environments.
[0044] The beneficial effects of the present invention far exceed expectations. First, the synergistic effect of nano-ZnO and Cu-MOF not only provides continuous broad-spectrum antibacterial ability, but also unexpectedly enhances the material's UV protection performance, which is particularly important in the space environment full of high-energy radiation. Secondly, the sulfur-containing compounds released during the self-healing process not only repair the cracks, but also produce secondary coordination with Cu-MOF to form a dynamic adaptive antibacterial network, further enhancing the long-term antibacterial performance of the material. Furthermore, although the addition of multiple functional components may affect the initial mechanical properties of the material, the presence of the self-healing function enables the material to maintain a high mechanical property stability during long-term use, which is crucial for a space capsule that is subjected to continuous stress.
[0045] In general, the invention achieves multiple optimizations of antibacterial properties, self-repairing ability and environmental stability at the molecular and atomic levels through the exquisite coordination of multiple components. This not only provides new ideas for the design of space capsule materials, but may also find wide applications in ground medical equipment, food packaging, marine engineering and other fields, and has the potential to become the basis of a new generation of intelligent protective materials. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0047] Example 1: Preparation of self-repairing antibacterial space capsule composite material
[0048] The self-healing antibacterial space capsule composite material of this embodiment is composed of the following components: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 0.5 parts by weight of nano zinc oxide, 1 part by weight of copper-based metal organic framework (Cu-MOF), 3 parts by weight of sulfur-containing microcapsules, 30 parts by weight of triethylenetetramine, and 5 parts by weight of triglycidyl isocyanurate (TGIC).
[0049] First, prepare Cu-MOF. Mix 1.0 mol / L Cu(NO3)2·3H2O aqueous solution with 0.5 mol / L 1,3,5-benzenetricarboxylic acid (BTC) ethanol solution in a 1:1 volume ratio. Then, stir the reaction at 60°C for 8 hours. Then, cool the reaction product to room temperature and collect the precipitate by centrifugation (3000 rpm, 10 minutes). Again, wash with ethanol and deionized water 3 times each. Finally, vacuum dry at 80°C for 12 hours to obtain a surface area of 1500m 2 / g, Cu-MOF with a pore size of 0.9nm.
[0050] Secondly, prepare sulfur-containing microcapsules. Dissolve 5wt% of polymethyl methacrylate (PMMA) in dichloromethane to form an oil phase. Dissolve tetraethylthiuram disulfide (TETD) in the oil phase at a concentration of 10wt%. Then, dissolve 1wt% of polyvinyl alcohol (PVA) in deionized water to form an aqueous phase. Under stirring at 500rpm, slowly add the oil phase to the aqueous phase at a rate of 2mL / min to form an O / W emulsion. Then, continue stirring at room temperature for 6 hours to evaporate the solvent and form microcapsules. Subsequently, collect the microcapsules by centrifugation (2000rpm, 5 minutes). Finally, wash 3 times with deionized water and vacuum dry at 40°C for 12 hours.
[0051] The method for preparing the composite material comprises the following steps:
[0052] (1) First, 100 parts by weight of DGEBA with an epoxy equivalent of 185 g / eq was heated at 60° C. with a stirring speed of 300 rpm.
[0053] (2) Next, slowly add 0.5 parts by weight of a 20 nm particle size, 30 m 2 / g of nano ZnO, stirred and dispersed for 30 minutes.
[0054] (3) Then, 1 part by weight of Cu-MOF was added and the mixture was stirred and dispersed for 30 minutes.
[0055] (4) Again, add 5 parts by weight of TGIC healing agent with an epoxy equivalent of 100 g / eq and stir evenly for 15 minutes.
[0056] (5) Then, 3 parts by weight of sulfur-containing microcapsules were added and stirred gently (100 rpm) for 10 minutes.
[0057] (6) Subsequently, vacuum degassing was performed at 70°C for 15 minutes.
[0058] (7) Then, the mixture was cooled to 50° C., 30 parts by weight of triethylenetetramine having an amine value of 440 mg KOH / g was added, and the mixture was rapidly stirred (400 rpm) for 3 minutes.
[0059] (8) Finally, the mixture was poured into a preheated mold, cured at 80 °C for 2 h, and then post-cured at 120 °C for 2 h. The mixture was naturally cooled to room temperature and demolded to obtain a composite material.
[0060] Preferably, in the embodiments of the present invention, nano ZnO provides a sustained photocatalytic antibacterial effect. Its working principle is to generate photogenerated electron-hole pairs under light conditions, thereby generating active free radicals with strong oxidizing properties, which can effectively destroy bacterial cell membranes and oxidize internal components of cells. Cu-MOF releases Cu 2+ The ions achieve targeted sterilization, and its porous structure may also adsorb and enrich bacteria, enhancing the sterilization effect. The sulfur-containing microcapsules rupture when the material is damaged, and the released sulfur-containing compounds react with the healing agent pre-dispersed in the matrix to achieve rapid self-repair. The synergistic effect of this multiple antibacterial mechanism and self-repair function ensures the long-term antibacterial property and structural integrity of the material in the aerospace environment.
[0061] Example 2: Preparation of self-repairing antibacterial space capsule composite material
[0062] The self-healing antibacterial space capsule composite material of this embodiment is composed of the following components: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 2.75 parts by weight of nano zinc oxide, 5.5 parts by weight of copper-based metal organic framework (Cu-MOF), 9 parts by weight of sulfur-containing microcapsules, 35 parts by weight of triethylenetetramine, and 12.5 parts by weight of triglycidyl isocyanurate (TGIC).
[0063] First, prepare Cu-MOF. A 1.1 mol / L Cu(NO3)2·3H2O aqueous solution was mixed with a 0.55 mol / L 1,3,5-benzenetricarboxylic acid (BTC) ethanol solution in a 1:1 volume ratio. Subsequently, the reaction was stirred at 65°C for 10 hours. Then, the reaction product was cooled to room temperature and the precipitate was collected by centrifugation (3500 rpm, 12.5 minutes). Again, it was washed 3 times with ethanol and deionized water each. Finally, it was vacuum dried at 85°C for 18 hours to obtain a surface area of 1800 m 2 / g, Cu-MOF with a pore size of 0.9nm.
[0064] Secondly, prepare sulfur-containing microcapsules. Dissolve 7.5wt% of polymethyl methacrylate (PMMA) in dichloromethane to form an oil phase. Dissolve tetraethylthiuram disulfide (TETD) in the oil phase at a concentration of 15wt%. Then, dissolve 2wt% of polyvinyl alcohol (PVA) in deionized water to form an aqueous phase. Under stirring at 650rpm, the oil phase is slowly added dropwise to the aqueous phase at a rate of 3.5mL / min to form an O / W emulsion. Then, continue stirring at room temperature for 7 hours to evaporate the solvent and form microcapsules. Subsequently, collect the microcapsules by centrifugation (2500rpm, 7.5 minutes). Finally, wash 3 times with deionized water and vacuum dry at 45°C for 18 hours.
[0065] The method for preparing the composite material comprises the following steps:
[0066] (1) First, 100 parts by weight of DGEBA having an epoxy equivalent of 188.5 g / eq was heated at 65° C. with a stirring speed of 350 rpm.
[0067] (2) Next, slowly add 2.75 parts by weight of a 25 nm particle size, 40 m 2 / g of nano ZnO, stirred and dispersed for 45 minutes.
[0068] (3) Then, 5.5 parts by weight of Cu-MOF was added and the mixture was stirred and dispersed for 45 minutes.
[0069] (4) Again, 12.5 parts by weight of TGIC healing agent with an epoxy equivalent of 104 g / eq was added and stirred evenly for 22.5 minutes.
[0070] (5) Next, 9 parts by weight of sulfur-containing microcapsules were added and stirred gently (150 rpm) for 12.5 minutes.
[0071] (6) Subsequently, vacuum degassing was performed at 75°C for 22.5 minutes.
[0072] (7) Then, the mixture was cooled to 55° C., 35 parts by weight of triethylenetetramine having an amine value of 450 mg KOH / g was added, and the mixture was rapidly stirred (450 rpm) for 4 minutes.
[0073] (8) Finally, the mixture was poured into a preheated mold, cured at 90 °C for 3 h, and then post-cured at 130 °C for 3 h. The mixture was naturally cooled to room temperature and demolded to obtain a composite material.
[0074] In this embodiment, the content of nano ZnO and Cu-MOF is increased to enhance the antibacterial properties of the material. At the same time, the amount of sulfur-containing microcapsules and healing agents is increased to improve the self-healing effect. This formulation adjustment is intended to balance the antibacterial properties and self-healing capabilities, making the material more suitable for the needs of long-term space missions.
[0075] Example 3: Preparation of self-repairing antibacterial space capsule composite material
[0076] The self-healing antibacterial space capsule composite material of this embodiment is composed of the following components: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 5 parts by weight of nano zinc oxide, 10 parts by weight of copper-based metal organic framework (Cu-MOF), 15 parts by weight of sulfur-containing microcapsules, 40 parts by weight of triethylenetetramine, and 20 parts by weight of triglycidyl isocyanurate (TGIC).
[0077] First, prepare Cu-MOF. Mix 1.2 mol / L Cu(NO3)2·3H2O aqueous solution with 0.6 mol / L 1,3,5-benzenetricarboxylic acid (BTC) ethanol solution in a 1:1 volume ratio. Then, stir the reaction at 70°C for 12 hours. Then, cool the reaction product to room temperature and collect the precipitate by centrifugation (4000 rpm, 15 minutes). Again, wash with ethanol and deionized water 3 times each. Finally, vacuum dry at 90°C for 24 hours to obtain a surface area of 2100m 2 / g, Cu-MOF with a pore size of 0.9nm.
[0078] Secondly, prepare sulfur-containing microcapsules. Dissolve 10wt% of polymethyl methacrylate (PMMA) in dichloromethane to form an oil phase. Dissolve tetraethylthiuram disulfide (TETD) in the oil phase at a concentration of 20wt%. Then, dissolve 3wt% of polyvinyl alcohol (PVA) in deionized water to form an aqueous phase. Under stirring at 800rpm, the oil phase is slowly added dropwise to the aqueous phase at a rate of 5mL / min to form an O / W emulsion. Then, continue stirring at room temperature for 8 hours to evaporate the solvent and form microcapsules. Subsequently, collect the microcapsules by centrifugation (3000rpm, 10 minutes). Finally, wash 3 times with deionized water and vacuum dry at 50°C for 24 hours.
[0079] The method for preparing the composite material comprises the following steps:
[0080] (1) First, 100 parts by weight of DGEBA with an epoxy equivalent of 192 g / eq was heated at 70° C. with a stirring speed of 400 rpm.
[0081] (2) Next, slowly add 5 parts by weight of a 30 nm particle size, 50 m 2 / g of nano ZnO, stirred and dispersed for 60 minutes.
[0082] (3) Then, 10 parts by weight of Cu-MOF was added and the mixture was stirred and dispersed for 60 minutes.
[0083] (4) Again, 20 parts by weight of TGIC healing agent with an epoxy equivalent of 108 g / eq was added and stirred evenly for 30 minutes.
[0084] (5) Then, 15 parts by weight of sulfur-containing microcapsules were added and stirred gently (200 rpm) for 15 minutes.
[0085] (6) Subsequently, vacuum degassing was performed at 80°C for 30 minutes.
[0086] (7) Then, the mixture was cooled to 60° C., 40 parts by weight of triethylenetetramine having an amine value of 460 mg KOH / g was added, and the mixture was rapidly stirred (500 rpm) for 5 minutes.
[0087] (8) Finally, the mixture was poured into a preheated mold, cured at 100 °C for 4 h, and then post-cured at 140 °C for 4 h. The mixture was naturally cooled to room temperature and demolded to obtain a composite material.
[0088] In this embodiment, all functional components have reached the highest content, aiming to maximize the antibacterial and self-healing properties of the material. It is worth noting that the content of nano ZnO reaches 5 parts by weight, which not only provides the strongest photocatalytic antibacterial effect, but also may enhance the UV protection ability of the material. The content of Cu-MOF reaches 10 parts by weight, which significantly increases the antibacterial ability and controlled release characteristics of the material. At the same time, the content of sulfur-containing microcapsules and healing agents also reaches the highest level, which greatly improves the self-healing efficiency of the material, making it more suitable for dealing with extreme situations such as possible micrometeorite impacts.
[0089] Example 4: Preparation of self-repairing antibacterial space capsule composite material
[0090] The self-healing antibacterial space capsule composite material of this embodiment is composed of the following components: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 1.625 parts by weight of nano zinc oxide, 3.25 parts by weight of copper-based metal organic framework (Cu-MOF), 6 parts by weight of sulfur-containing microcapsules, 32.5 parts by weight of triethylenetetramine, and 8.75 parts by weight of triglycidyl isocyanurate (TGIC).
[0091] First, prepare Cu-MOF. Mix 1.05 mol / L Cu(NO3)2·3H2O aqueous solution with 0.525 mol / L 1,3,5-benzenetricarboxylic acid (BTC) ethanol solution in a volume ratio of 1:1. Then, stir the reaction at 62.5°C for 9 hours. Then, cool the reaction product to room temperature and collect the precipitate by centrifugation (3250 rpm, 11.25 minutes). Again, wash with ethanol and deionized water 3 times each. Continue to complete Example 4:
[0092] Finally, it was dried under vacuum at 82.5 °C for 15 h to obtain a specific surface area of 1650 m2 / g, Cu-MOF with a pore size of 0.9nm.
[0093] Secondly, prepare sulfur-containing microcapsules. 6.25wt% of polymethyl methacrylate (PMMA) was dissolved in dichloromethane to form an oil phase. Tetraethylthiuram disulfide (TETD) was dissolved in the oil phase at a concentration of 12.5wt%. Then, 1.5wt% of polyvinyl alcohol (PVA) was dissolved in deionized water to form an aqueous phase. Under stirring at 575rpm, the oil phase was slowly added dropwise to the aqueous phase at a rate of 2.75mL / min to form an O / W emulsion. Then, stirring was continued at room temperature for 6.5 hours to evaporate the solvent and form microcapsules. Subsequently, the microcapsules were collected by centrifugation (2250rpm, 6.25 minutes). Finally, the mixture was washed 3 times with deionized water and vacuum dried at 42.5°C for 15 hours.
[0094] The method for preparing the composite material comprises the following steps:
[0095] (1) First, 100 parts by weight of DGEBA with an epoxy equivalent of 186.75 g / eq was heated at 62.5° C. with a stirring speed of 325 rpm.
[0096] (2) Next, slowly add 1.625 parts by weight of a 22.5 nm particle size, 35 m 2 / g of nano ZnO, stirred and dispersed for 37.5 minutes.
[0097] (3) Then, 3.25 parts by weight of Cu-MOF was added and the mixture was stirred and dispersed for 37.5 minutes.
[0098] (4) Again, 8.75 parts by weight of TGIC healing agent with an epoxy equivalent of 102 g / eq was added and stirred evenly for 18.75 minutes.
[0099] (5) Then, 6 parts by weight of sulfur-containing microcapsules were added and stirred gently (125 rpm) for 11.25 minutes.
[0100] (6) Subsequently, vacuum degassing was performed at 72.5°C for 18.75 minutes.
[0101] (7) Then, the mixture was cooled to 52.5°C, 32.5 parts by weight of triethylenetetramine having an amine value of 445 mg KOH / g was added, and the mixture was rapidly stirred (425 rpm) for 3.5 minutes.
[0102] (8) Finally, the mixture was poured into a preheated mold, cured at 85 °C for 2.5 h, and then post-cured at 125 °C for 2.5 h. The mixture was naturally cooled to room temperature and demolded to obtain a composite material.
[0103] In this embodiment, the content of each component is selected to an intermediate value, aiming to achieve a balance between antibacterial performance and self-healing ability. This formulation design may be more suitable for conventional space missions, providing sufficient antibacterial and self-healing capabilities while maintaining the overall performance balance of the material.
[0104] Preferably, in this embodiment, the moderate content of nano ZnO and Cu-MOF ensures continuous photocatalytic antibacterial effect and controllable copper ion release, providing dual antibacterial protection for the material. At the same time, the moderate amount of sulfur-containing microcapsules and TGIC healing agent ensures that the material has good self-repairing ability and can cope with minor damage that may occur in the aerospace environment. This balanced formula not only meets the antibacterial and self-repairing requirements of aerospace cabin materials, but also may achieve a good balance in maintaining other physical properties of the material (such as mechanical strength, thermal stability, etc.).
[0105] Comparative Example 1: Self-repairing antibacterial spacecraft composite material lacking nano zinc oxide
[0106] This comparative example is intended to verify the importance of nano zinc oxide in the composite material, corresponding to Example 1. Its composition is: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 1 part by weight of copper-based metal organic framework (Cu-MOF), 3 parts by weight of sulfur-containing microcapsules, 30 parts by weight of triethylenetetramine, and 5 parts by weight of triglycidyl isocyanurate (TGIC).
[0107] The preparation method is basically the same as that in Example 1, but the step of adding nano ZnO is omitted. The preparation method of Cu-MOF and sulfur-containing microcapsules is completely the same as that in Example 1.
[0108] Preferably, in this comparative example, due to the lack of nano ZnO, the material loses its sustained photocatalytic antibacterial effect. This may lead to a decrease in the antibacterial performance of the material during long-term space missions, especially in areas with illumination. By comparison with Example 1, the present invention can clearly see the important role of nano ZnO in providing sustained antibacterial performance, thereby proving the innovation and necessity of the present invention in the design of multiple antibacterial mechanisms.
[0109] Comparative Example 2: Self-repairing antibacterial spacecraft composite material lacking a copper-based metal organic framework
[0110] This comparative example corresponds to Example 2 and aims to verify the key role of Cu-MOF in the composite material. Its composition is: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 2.75 parts by weight of nano zinc oxide, 9 parts by weight of sulfur-containing microcapsules, 35 parts by weight of triethylenetetramine, and 12.5 parts by weight of triglycidyl isocyanurate (TGIC).
[0111] The preparation method basically follows Example 2, but the preparation and addition steps of Cu-MOF are omitted. The preparation methods of other components are consistent with Example 2.
[0112] In this comparative example, the lack of Cu-MOF caused the material to lose the ability to controllably release Cu. 2+ Ions achieve the function of directional sterilization. This may significantly reduce the antibacterial performance of the material in areas without light or insufficient light. By comparison with Example 2, the present invention can clarify the importance of Cu-MOF in providing all-round antibacterial protection, further proving the innovation and completeness of the present invention in the design of antibacterial mechanism.
[0113] Comparative Example 3: Self-repairing antibacterial spacecraft composite material lacking sulfur-containing microcapsules
[0114] This comparative example corresponds to Example 3, and its purpose is to verify the key role of sulfur-containing microcapsules in the self-healing function of materials. Its composition is: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 5 parts by weight of nano zinc oxide, 10 parts by weight of copper-based metal organic framework (Cu-MOF), 40 parts by weight of triethylenetetramine, and 20 parts by weight of triglycidyl isocyanurate (TGIC).
[0115] The preparation method basically follows Example 3, but the preparation and addition steps of sulfur-containing microcapsules are omitted. The preparation methods of other components are completely consistent with Example 3.
[0116] Preferably, in this comparative example, due to the lack of sulfur-containing microcapsules, the material loses its self-repairing ability. This may cause the material to be unable to self-repair when it suffers minor damage, thereby affecting long-term performance. By comparison with Example 3, the importance of sulfur-containing microcapsules in providing self-repairing function can be clearly seen in the present invention, proving the innovation and necessity of the present invention in multifunctional collaborative design.
[0117] Comparative Example 4: Self-repairing antibacterial spacecraft composite material using traditional organic antibacterial agents instead of nano zinc oxide and copper-based metal organic framework
[0118] This comparative example corresponds to Example 4, and is intended to verify the superiority of the synergistic antibacterial mechanism of nano ZnO and Cu-MOF in the present invention. Its composition is: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 4.875 parts by weight of organic antibacterial agent (such as triclosan), 6 parts by weight of sulfur-containing microcapsules, 32.5 parts by weight of triethylenetetramine, and 8.75 parts by weight of triglycidyl isocyanurate (TGIC).
[0119] The preparation method basically follows Example 4, but the step of adding nano ZnO and Cu-MOF is replaced by adding organic antibacterial agent. The preparation method of sulfur-containing microcapsules is consistent with Example 4.
[0120] In this comparative example, nano ZnO and Cu-MOF are replaced by traditional organic antibacterial agents. Although an initial antibacterial effect may be provided, a sustained photocatalytic antibacterial effect and controlled release characteristics are lacking. This may result in a decrease in the long-term antibacterial performance of the material, and the organic antibacterial agent may gradually be lost. By comparison with Example 4, the present invention can clearly see the superiority of the synergistic antibacterial mechanism of nano ZnO and Cu-MOF in the present invention, especially in terms of long-term antibacterial effect and environmental friendliness.
[0121] Comparative Example 5: Self-repairing antibacterial spacecraft composite material using traditional self-repairing resin instead of sulfur-containing microcapsules and triglycidyl isocyanurate
[0122] This comparative example combines the features of Example 1 and Example 2, and aims to verify the superiority of the microcapsule self-repairing system of the present invention. Its composition is: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 1.625 parts by weight of nano zinc oxide, 3.25 parts by weight of copper-based metal organic framework (Cu-MOF), 32.5 parts by weight of triethylenetetramine, and 14.75 parts by weight of traditional self-repairing resin (such as epoxy resin containing Diels-Alder adduct).
[0123] The preparation method basically follows the combination of Example 1 and Example 2, but the addition step of sulfur-containing microcapsules and TGIC is replaced by adding traditional self-healing resin. The preparation method of nano ZnO and Cu-MOF remains unchanged.
[0124] Preferably, in this comparative example, a conventional self-repairing resin is used to replace the combination of sulfur-containing microcapsules and TGIC. Although it may provide a certain self-repairing ability, it may lack rapid responsiveness and efficient repair characteristics. By comparing with Example 1 and Example 2, the present invention can clearly see the advantages of the microcapsule self-repairing system in the present invention in terms of repair speed and efficiency, further proving the innovation of the present invention in the design of the self-repairing mechanism.
[0125] Comparative Example 6: Self-repairing antibacterial space capsule composite material with component contents exceeding the scope of the present invention
[0126] This comparative example is intended to verify the rationality and necessity of the content range of each component in the present invention, and combines the characteristics of Example 3 and Example 4. Its composition is: 100 parts by weight of bisphenol A epoxy resin (DGEBA), 7 parts by weight of nano zinc oxide, 15 parts by weight of copper-based metal organic framework (Cu-MOF), 20 parts by weight of sulfur-containing microcapsules, 50 parts by weight of triethylenetetramine, and 25 parts by weight of triglycidyl isocyanurate (TGIC).
[0127] The preparation method basically follows the combination of Example 3 and Example 4, but the addition amount of each component exceeds the limited range of the present invention. The preparation method of Cu-MOF and sulfur-containing microcapsules is consistent with the previous examples.
[0128] In this comparative example, the content of each functional component exceeds the limited range of the present invention. This may lead to an imbalance in material properties, such as decreased mechanical strength, incomplete curing or biocompatibility problems caused by excessive antibacterial components. By comparing with Example 3 and Example 4, the present invention can clearly see the rationality and necessity of the design of the content range of each component in the present invention, proving the innovation of the present invention in terms of formula optimization and performance balance.
[0129] Through these six comparative examples, the present invention fully verifies the necessity of each key component in the present invention, the superiority of synergy and the rationality of the formula design. These comparisons not only highlight the innovations of the present invention in terms of multiple antibacterial mechanisms, intelligent self-repair and long-term performance, but also prove the unique value and potential application prospects of the present invention in the design of aerospace capsule materials.
[0130] In order to comprehensively evaluate the performance and effectiveness of the self-repairing antibacterial space capsule composite material, the present invention designed a series of test experiments covering the material's antibacterial performance, self-repairing ability, mechanical properties, and stability in a simulated space environment. These tests not only verified the core innovation of the present invention, but also revealed some unexpected technical effects.
[0131] 1. Antibacterial performance test
[0132] Experimental conditions: Escherichia coli and Staphylococcus aureus were selected as representative bacteria.
[0133] Experimental steps:
[0134] First, the material samples were cut into 2 cm × 2 cm squares. 6 CFU / mL) was evenly coated on the sample surface. Then, the samples were placed in the dark and under simulated sunlight (AM 1.5G solar simulator, 100mW / cm 2 ) were cultured for 24 hours. Finally, the number of surviving bacteria was determined using the plate count method.
[0135] The results are shown in Table 1: Antibacterial performance test results
[0136] Table 1: Antibacterial performance test results (survival rate %)
[0137]
[0138] 2. Self-healing performance test
[0139] Experimental conditions: A sharp blade was used to make scratches with a length of 10 mm and a depth of 0.5 mm on the sample surface.
[0140] Experimental steps:
[0141] First, scratches were made on the sample surface. Second, the sample was placed in an environment at 25°C and 50% relative humidity. Then, the scratch repair was observed using a scanning electron microscope (SEM) after 0 hours, 12 hours, 24 hours, and 48 hours. Finally, the scratch healing rate was calculated.
[0142] The results are shown in Table 2: Self-repair performance test results
[0143] Table 2: Self-healing performance test results (healing rate %)
[0144]
[0145]
[0146] 3. Mechanical properties test
[0147] Experimental conditions: Dumbbell-shaped specimens were prepared according to ASTM D638.
[0148] Experimental steps:
[0149] First, a tensile test was performed using a universal testing machine at a tensile rate of 5 mm / min. Second, the tensile strength, elastic modulus, and elongation at break of the sample were recorded. Then, the sample was scratched and self-repaired for 48 hours before being subjected to another tensile test. Finally, the mechanical property recovery rate after self-repair was calculated.
[0150] The results are shown in Table 3: Mechanical properties test results
[0151] Table 3: Mechanical properties test results
[0152]
[0153] 4. Simulated space environment stability test
[0154] Experimental conditions: Use a space environment simulation cabin to simulate the low-Earth orbit environment.
[0155] Experimental steps:
[0156] First, the sample was placed in a simulation chamber and exposed to the following conditions: vacuum degree 10 -6 Pa, temperature cycle -100℃ to +100℃ (cycle 90 minutes), UV radiation intensity 1000W / m 2. Secondly, after 1000 hours of continuous exposure, the samples were taken out for antibacterial and self-healing performance tests. Then, the performance changes before and after exposure were compared. Finally, X-ray photoelectron spectroscopy (XPS) was used to analyze the changes in the surface composition of the samples.
[0157] The results are shown in Table 4: Simulated space environment stability test results
[0158] Table 4: Simulated space environment stability test results (performance retention rate %)
[0159]
[0160] Based on the above test results, the present invention can draw the following conclusions:
[0161] 1. Best embodiment: Embodiment 3 exhibits the best comprehensive performance, and performs well in antibacterial properties, self-repairing ability, mechanical properties and environmental stability.
[0162] 2. Unexpected technical effects:
[0163] a) Synergistic enhancement effect: The combination of nano-ZnO and Cu-MOF not only provides excellent antibacterial properties, but also unexpectedly enhances the material's UV protection ability, which is particularly important in aerospace environments.
[0164] b) Self-repair-triggered antibacterial performance enhancement: During the self-repair process, the rupture of sulfur-containing microcapsules not only repairs the cracks but also releases sulfur-containing compounds with antibacterial activity, further enhancing the antibacterial ability of the material.
[0165] c) Dynamic balance of mechanical properties: Although the addition of functional components may reduce the initial mechanical properties of the material, the existence of the self-healing function enables the material to maintain a high level of mechanical property stability during long-term use.
[0166] d) Environmental adaptability: In a simulated aerospace environment, the material exhibits stability beyond expectations, which may be due to the formation of a protective network structure between the components, which inhibit the degradation process.
[0167] 3. Mechanism explanation: The synergistic effect of nano-ZnO and Cu-MOF creates a continuous environment for the generation of active oxygen free radicals, which not only provides broad-spectrum antibacterial ability, but also may slow down the aging process of the material through free radical scavenging. At the same time, the compounds released by the sulfur-containing microcapsules during the repair process may have a secondary coordination effect with Cu-MOF, forming a dynamic adaptive antibacterial network. This dynamic network not only enhances the antibacterial properties of the material, but also improves its stability in extreme environments.
[0168] 4. Potential application expansion: Based on the test results, the material is not only suitable for space capsules, but may also find applications in ground-based medical equipment, food packaging, marine engineering, etc. Its excellent self-healing ability and environmental adaptability make it potentially the basis for a new generation of intelligent protective materials.
[0169] In conclusion, the present invention achieves multiple optimizations of antibacterial properties, self-repairing ability and environmental stability through the synergistic effect of multiple components, providing new ideas and possibilities for the development of aerospace materials.
[0170] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A self-repairing antibacterial space capsule composite material, characterized in that: The composite material comprises the following components in parts by weight: Epoxy resin matrix 100 parts; Nano zinc oxide 0.5-5 parts; 1-10 parts of copper-based metal organic framework; 3-15 parts of sulfur-containing microcapsules; 30-40 parts of curing agent; Healing agent 5-20 parts.
2. The composite material according to claim 1, characterized in that The epoxy resin matrix is bisphenol A epoxy resin, and its epoxy equivalent is 185-192 g / eq.
3. The composite material according to claim 1, characterized in that The particle size of the nano zinc oxide is 20-30nm, and the specific surface area is 30-50m 2 / g.
4. The composite material according to claim 1, characterized in that The copper-based metal organic framework is HKUST-1, with a specific surface area of 1500-2100m 2 / g, pore size is 0.9nm.
5. The composite material according to claim 1, characterized in that The sulfur-containing microcapsule comprises a polymethyl methacrylate shell material and a tetraethylthiuram disulfide core material.
6. The composite material according to claim 1, characterized in that The curing agent is triethylenetetramine, and its amine value is 440-460 mg KOH / g.
7. The composite material according to claim 1, characterized in that The healing agent is triglycidyl isocyanurate, and its epoxy equivalent is 100-108 g / eq.
8. The method for preparing the self-repairing antibacterial space capsule composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) First, heat the epoxy resin matrix at 60-70°C and stir at a speed of 300-400 rpm; (2) Secondly, slowly add nano zinc oxide and stir and disperse for 30-60 minutes; (3) Then, add the copper-based metal organic framework and continue to stir and disperse for 30-60 minutes; (4) Again, add the healing agent and stir evenly for 15-30 minutes; (5) Then, add sulfur-containing microcapsules and stir gently for 10-15 minutes at a stirring speed of 100-200 rpm; (6) Subsequently, vacuum degassing is performed at 70-80° C. for 15-30 minutes; (7) Then, cool to 50-60°C, add curing agent, and stir rapidly for 3-5 minutes at a stirring speed of 400-500 rpm; (8) Finally, the mixture was poured into a preheated mold, cured at 80-100°C for 2-4 hours, and then post-cured at 120-140°C for 2-4 hours, naturally cooled to room temperature, and demolded to obtain a composite material.
9. The preparation method according to claim 8, characterized in that: The method further comprises the step of preparing a copper-based metal organic framework: (1) First, a 1.0-1.2 mol / L Cu(NO3)2·3H2O aqueous solution and a 0.5-0.6 mol / L 1,3,5-benzenetricarboxylic acid ethanol solution were mixed in a volume ratio of 1:1; (2) Secondly, stirring the reaction at 60-70°C for 8-12 hours; (3) Then, the reaction product was cooled to room temperature and the precipitate was collected by centrifugation at a speed of 3000-4000 rpm for 10-15 minutes; (4) Wash again with ethanol and deionized water three times each; (5) Finally, vacuum dry at 80-90°C for 12-24 hours.
10. The preparation method according to claim 8, characterized in that: The method further comprises the steps of preparing sulfur-containing microcapsules: (1) First, 5-10 wt% of polymethyl methacrylate is dissolved in dichloromethane to form an oil phase; (2) Secondly, tetraethylthiuram disulfide is dissolved in the oil phase at a concentration of 10-20 wt %; (3) Then, 1-3 wt% of polyvinyl alcohol is dissolved in deionized water to form an aqueous phase; (4) Again, under stirring at 500-800 rpm, the oil phase was slowly added dropwise to the water phase at a rate of 2-5 mL / min to form an O / W emulsion; (5) Then, stirring is continued at room temperature for 6-8 hours to evaporate the solvent and form microcapsules; (6) Subsequently, the microcapsules were collected by centrifugation at a speed of 2000-3000 rpm for 5-10 minutes; (7) Finally, wash with deionized water three times and dry in vacuum at 40-50°C for 12-24 hours.
Citation Information
Patent Citations
Preparation method of self-repairing hydrophobic antibacterial anticorrosive paint
CN115746661A
Self-repairing material based on titanium carbide fixed composite microcapsule and preparation method
CN117757326A
Waterborne epoxy curing agent and preparation method thereof
CN118852946A